An assessment of the adequacy of the National Social Security scheme with particular reference to retirement and survivor’s benefits at University of Zimbabwe - Mubanga, R (2014)
This study sought to assess the adequacy of the retirement and survivors benefits under National Social Security Scheme. The focus of the study was the retirement and survivors’ benefits. Thirty five people were identified through the University of Zimbabwe pension’s office. Of these, 15 were getting retirement benefits and the rest i.e. were getting survivors’ benefits giving a response rate of 53% and 75% for retirement and survivors’ benefits respectively. In addition, ten employees were also interviewed, five female and five male. Furthermore,a representative from ZCTU responsible for pension issues and an official from NSAA were interviewed. The research established that benefits that are being paid out by NSSA are not inadequate when compared with the monthly basket figures that are produced by the Consumer Council of Zimbabwe. Of late the monthly basket is pegged in hard currency and stands at US$280 for a family of six and yet NSSA pays Z$100 trillion (Z$100 revalued) for retirement and Z$44 trillion (Z$44 revalued) for invalidity, survivors’ benefit and Z$1 quadrillion (Z$1 000.00) for funeral grant. The benefits that are being paid are nowhere near the monthly basket which is in hard currency. NSSA is there to provide minimum benefits and minimum benefits must that ensure that a pensioner or the survivors must be able to get basic commodities from the payment. It is also important for NSSA to work closely with the workers and their representatives. Instead of relying on representative bodies they should also visit work places to educate workers and also get information on the expectations of the workers. For instance, this study established that workers expect NSSA to work with local authorities in building houses for them.When this is considered from the Human Resource Management point of view, it is a valid expectation. Employers are expected to look after their workforce during and after their 2 working lives and that can be achieved through pension schemes. In this instance government so it necessary to make provisions for workers when they lose income through injury, retirement and so on and came up with a national program NSSA and this noble move is commendable. The study also established that workers expect NSSA to provide cheap accommodation so that they retire they are proud owners of hours. This issue of provision of accommodation was not part of the study butit was raised by most of the workers interviewed including the labour body representatives. Officials from NSSA then indicated that they are working on such aproject in Marondera but the workers including the researcher are not aware of such programs. It is the view of the researcher that such programs should be spread all over the country and not benefit one or two provinces only. NSSA can work with local authorities who will identify pieces of land and NSSA can then service the land and build houses using personnel in the army, policy, building brigades and prisoners.